Ambivalent Encounters Childhood, Tourism, and Social Change in Banaras, India - Huberman, Jenny (Rutgers Series in Childhood Studies, 2012)
Jenny Huberman provides an ethnographic study of encounters between western tourists and the children who work as unlicensed peddlers and guides along the riverfront city of Banaras, India. She examines how and why these children elicit such powerful reactions from western tourists and locals in their community as well as how the children themselves experience their work and render it meaningful.Ambivalent Encounters brings together scholarship on the anthropology of childhood, tourism, consumption, and exchange to ask why children emerge as objects of the international tourist gaze; what role they play in representing socio-economic change; how children are valued and devalued; why they elicit anxieties, fantasies, and debates; and what these tourist encounters teach us more generally about the nature of human interaction.